Specimen retrieving needle - Perdrizet, George; Brautigam, Robert; Brautigam, Richard (2003)
A specimen retrieving needle is in the form of an elongated body having a closed lead end. At least one cutting blade is formed on the body. The blade has a sharpened edge so as to remove a specimen from an internal organ. The needle is ultrathin to minimize tissue trauma and to reduce the risk of hemorrhage and organ damage.